Did Russia’s invasion of Ukraine unite Europe? Cohesion and divisions of the European Parliament on Twitter - Juliana Chueri; Petter Törnberg (Political Research Exchange, 2024)
The EU has been on track toward growing disunity along geographical and political lines, expressed in growing anti-EU sentiments and the rise of Euroskeptic forces. However, Russia’s invasion of Ukraine seems to have functioned as a source of unity – revitalizing the European project by creating alliances in response to an external threat. However, as the war drags on, it begs the question of how brittle its new-found unity may be. This study thus seeks to examine the extent to which the war has mended the geographical and political divisions in the EU. Focusing on elite cohesion, we analyse social media interaction to provide a relational view of the alliances of the members of the European Parliament. We find that parliamentarians did not become more cohesive: East-Western division remains pronounced, and Euroskeptic political groups became further isolated. These findings imply that Euroskeptic groups will likely continue to be a source of contestation inside of the European Union.